THE INDICATION OF UNFAIR BUSINESS COMPETITION PRACTICE IN THE IMPLEMENTATION OF PUBLIC PROCUREMENT AUCTION USING E-TENDERING - Muniroh, Siti Dhurotun; Kamal, Ubaidillah (Faculty of Law, Universitas Negeri Semarang, 2018)
Public Procurement or E-Procurement is one of the efforts to improve the quality of public services. Implementation of Public Procurement electronically at auctions is conducted through E-Tendering. Though it has been arranged with clear legal rules, there were still deviations in conducting the auctions of Public Procurement. One of the Ministry that organizes the auctions of Public Procurement through E-Tendering is the Regional Office of Ministry of Justice and Human Rights of Central Java. The researcher conducted a juridical study on the auctions of Public Procurement through E-Tendering with the research questions as follows: (1) How is the implementation of auctions of Public Procurement through E-Tendering at the Regional Office of Ministry of Justice and Human Rights of Central Java? (2) How is the indication of unfair competition practice done in the auction of Public Procurement through E-Tendering at the Regional Office of Ministry of Justice and Human Rights of Central Java? This research was Qualitative research based on empirical-juridical legal research approach. The results showed that the implementation process of the auctions of Public Procurement through E-Tendering in Procurement Services Unit (ULP) Regional Office of Ministry of Justice and Human Rights of Central Java has been in accordance with the Presidential Regulation Number 54 Years 2010 along with the changes and with the Chief of Department of Public Procurement Policies (LKPP) Regulation Number 1 Year 2015 about E-Tendering. Besides, the implementation of auctions of Public Procurement through E-Tendering on Procurement Services Unit (ULP) Regional Office of Ministry of Justice and Human Rights of Central Java has ever happened a horizontal conspiracy.